Middle class squeeze? Social class and perceived financial hardship in Ireland, 2002-2012 - Mühlau, Peter (Economic & Social Studies, 2014)
Ireland has been particularly hit by the economic downturn of 2008. For many families in Ireland the economic downturn put strong pressures on their household budgets. This study examines how the recession has changed class differences with regard to experiences of economic strain. It contrasts the “middle class squeeze” view that sees the “middle” or the “middling classes” as particularly hard hit by the economic downturn with the class theoretical point of view that the recession is expected to widen the gaps between classes with regard to their ability to maintain living standards and that working, not middle classes bear the largest strain on economic wellbeing. The study derives competing hypotheses from these views and tests them using data from the Irish leg of the European Social Survey. Key findings are that financial hardship increased most for the working classes and the class of own account workers and self-employed employees and that class differences with regard to unemployment and benefit dependency risks are the main explanatory mechanism.